Kang Le Xin Reduces Blood Pressure Through Inducing Endothelial-Dependent Vasodilation by Activating the AMPK-eNOS Pathway - Zhao, Yixiu; Zhu, Jiuxin; Liang, Hangfei; Yang, Shuang; Zhang, Yannan; Han, Weina; Chen, Chao; Cao, Na; Aruhan; Liang, Peiqiang; Du, Xing; Huang, Jian; et al. (Frontiers in Pharmacology, 2020)
Hypertension is a major risk factor for stroke and cardiovascular events in clinic, which is accompanied by the abnormality of vascular tone and endothelial dysfunction of small artery. Here we report that Kang Le Xin (KLX), a novel anthraquinones compound, could reduce blood pressure and the underlying mechanisms involves that KLX induces endothelium-dependent vasodilation. KLX significantly decreases the arterial blood pressure of spontaneous hypertensive rats (SHR), decreases the contractile reactivity of superior mesenteric artery to phenylephrine and increases the diastolic reactivity of superior mesenteric artery to carbachol in a dose-dependent manner. Besides, KLX reduces vascular tension of endothelium-intact mesenteric artery pre-constricted with phenylephrine in a dose-dependent manner, while this effect is inhibited by depriving vascular endothelium or pretreating vascular rings with L-NAME (endothelial nitric oxide synthase inhibitor) or compound C (AMP-activated protein kinase inhibitor). Moreover, KLX increases nitric oxide (NO) generation, endothelial nitric oxide synthase (eNOS) , AKT and AMP-activated protein kinase (AMPK) phosphorylation in cultured human umbilical vein endothelial cells (HUVECs), while these effects are inhibited by pretreating cells with compound C. In conclusion, KLX is a new compound with the pharmacological action of reducing arterial blood pressure. The underlying mechanism involves KLX induces endothelium-dependent vasodilation through activating AMPK-AKT-eNOS signaling pathway.